Electrophysiological correlates of observational learning in children. Issue 5 (12th June 2015) - Rodriguez Buritica, Julia M.; Eppinger, Ben; Schuck, Nicolas W.; Heekeren, Hauke R.; Li, Shu‐Chen
Abstract: Observational learning is an important mechanism for cognitive and social development. However, the neurophysiological mechanisms underlying observational learning in children are not well understood. In this study, we used a probabilistic reward‐based observational learning paradigm to compare behavioral and electrophysiological markers of individual and observational reinforcement learning in 8‐ to 10‐year‐old children. Specifically, we manipulated the amount of observable information as well as children's similarity in age to the observed person (same‐aged child vs. adult) to examine the effects of similarity in age on the integration of observed information in children. We show that the feedback‐related negativity (FRN) during individual reinforcement learning reflects the valence of outcomes of own actions. Furthermore, we found that the feedback‐related negativity during observational reinforcement learning (oFRN) showed a similar distinction between outcome valences of observed actions. This suggests that the oFRN can serve as a measure of observational learning in middle childhood. Moreover, during observational learning children profited from the additional social information and imitated the choices of their own peers more than those of adults, indicating that children have a tendency to conform more with similar others (e.g. their own peers) compared to dissimilar others (adults). Taken together, our results show that children can benefit from integrating observable information and that oFRN may serve as a measure of observational learning in children. Abstract : We showed that the oFRN differentiated between negative and positive observed action‐outcomes of others and may serve as a measure of observational learning in school‐aged children. Moreover, we found that the oFRN showed a trend of being larger when observing other children compared to observing adults.